Comparative Analysis of Monetary Policy Shocks and Exchange Rate Fluctuations in Nigeria and South Africa - A., Sulaiman L.; A., Lawal N.; O., Migiro S. (Journal of Economics and Behavioral Studies, 2018)
The study examined a comparative analysis of monetary policy shocks and exchange rate fluctuations based on evidence from the two largest economies in Africa (Nigeria and South Africa) – from 1985 to 2015. Data were derived from various sources which include the National Bureau of Statistics, the Central Banks reports and the World Bank database. Vector Autoregressive (VAR) Analysis was used as the estimation technique. The results indicated that the foreign interest rate in South Africa had higher variations in the short-run. While in the long-run, foreign interest rate has higher percentage variations to exchange rate. In Nigeria the world oil price has the higher influence on exchange rate both in the short-run and longrun periods. Based on these results, the study then recommended that the monetary authorities and policymakers in both countries encourage external currency inflows into the economy.